Let's complete the process of solving the equation step by step.
Given equation:
\[ 7b + 10 = 13b + 4 \]
Step 1: Isolate the variable term. To isolate the variable \( b \), we can start by subtracting \( 13b \) from both sides:
\[ 7b + 10 - 13b = 13b + 4 - 13b \]
This simplifies to:
\[ -6b + 10 = 4 \]
Descriptive terms:
- Subtract 13b from both sides
Step 2: Isolate the constant term. Next, subtract 10 from both sides:
\[ -6b + 10 - 10 = 4 - 10 \]
This simplifies to:
\[ -6b = -6 \]
Descriptive terms:
- Subtract 10 from both sides
Step 3: Solve for \( b \). Now, divide both sides by -6:
\[ b = \frac{-6}{-6} \]
This simplifies to:
\[ b = 1 \]
Descriptive terms:
- Divide both sides by -6
Final Answers:
- Equation for Step 2: \( -6b = -6 \)
- Final Value for \( b \): \( b = 1 \)
So your completed process is:
- \( 7b + 10 = 13b + 4 \)
- Subtract 13b from both sides
- \( -6b + 10 = 4 \)
- Subtract 10 from both sides
- \( -6b = -6 \)
- Divide both sides by -6
- \( b = 1 \)